2019
DOI: 10.1016/j.bbrep.2019.100630
|View full text |Cite|
|
Sign up to set email alerts
|

Von Willebrand Factor Type A domain of hCLCA1 is sufficient for U-937 macrophage activation

Abstract: The human hCLCA1 gene is a member of the CLCA gene family that has a well-documented role in inflammatory airway diseases. Previously, we demonstrated that secreted hCLCA1 plays a role in regulating the innate immune response by activating airway macrophages. However, the mechanism of this regulation remains unclear. In this present study, recombinant proteins containing different hCLCA1 domains are expressed to determine the specific hCLCA1 domain(s) responsible for macrophage activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Therefore, our observation that VWA_2 Pfam domains are largely confined to ComC proteins of Acinetobacter pathogens in the ACB clade makes it tempting to postulate that the addition of a VWA domain to the PTA is at least one determinant that turns T4aP into a virulence factor. In this context, the recent finding is interesting that VWA domains can activate of macrophages, central regulators of airway inflammation [79, 80].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our observation that VWA_2 Pfam domains are largely confined to ComC proteins of Acinetobacter pathogens in the ACB clade makes it tempting to postulate that the addition of a VWA domain to the PTA is at least one determinant that turns T4aP into a virulence factor. In this context, the recent finding is interesting that VWA domains can activate of macrophages, central regulators of airway inflammation [79, 80].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a vWFa domain was also found in PilY1 of P . aeruginosa [ 36 , 70 , 81 ], and supporting its role in bacterial virulence, it was subsequently found that vWFa domains can activate macrophages, central regulators of airway inflammation [ 82 , 83 ]. On the first sight, our findings that exclusively ComC of pathogenic Acinetobacter could be annotated with a Pfam VWA_2 domain suggest that the acquisition of a vWFa domain drives the conversion of T4aP into a virulence factor.…”
Section: Discussionmentioning
confidence: 99%
“…The c h l oride channel regulator , c alcium a ctivated ( CLCA ) gene family has been implicated in the pathophysiology of inflammatory airway diseases, such as asthma [ 1 3 ] or cystic fibrosis [ 4 6 ], tumor progression and metastasis [ 7 11 ]. In this context, different CLCA proteins have been linked to cellular functions including mucus processing [ 12 , 13 ], activation of airway macrophages [ 14 16 ], the modulation of the anion channel TMEM16A [ 17 , 18 ], cellular differentiation such as mucus cell metaplasia [ 1 , 19 – 21 ], cellular senescence and apoptosis [ 7 , 22 27 ], or as adhesion molecules for metastatic tumor cells [ 28 , 29 ]. Due to their proposed biomedical relevance, CLCA molecules have been studied in healthy and diseased humans [ 2 , 4 , 5 , 26 , 30 37 ] and mammalian model organisms including mouse [ 38 44 ], pig [ 45 49 ], horse [ 3 , 50 ], and cat [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%